2020
DOI: 10.3389/fneur.2020.555274
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cumulative Exposure to Increased Low-Density Lipoprotein Cholesterol and the Prevalence of Asymptomatic Intracranial Atherosclerotic Stenosis

Abstract: Background and Purpose: Intracranial atherosclerosis has gained increasing attention due to the high risk of recurrent clinical or subclinical ischemic events, while the relationship between low-density lipoprotein cholesterol (LDL-C) measured at a single time point and intracranial atherosclerotic stenosis (ICAS) is inconsistent. This study aims to assess the association between cumulative exposure to increased LDL-C and the prevalence of asymptomatic ICAS.Methods: The Asymptomatic Polyvascular Abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The possible mechanisms of Hcy and ICVD are as follows: (1) Hcy is able to damage vascular endothelium; (2) Hcy can stimulate the abnormal proliferation of vascular smooth muscle cells; (3) Hcy can cause platelet aggregation, change blood viscosity and increase blood coagulation; (4) Hcy is able to enhance the peroxidation of LDL-C, increase the production of LDL-C, accelerate the progression of atherosclerosis, hence aggravate the condition of ICVD [ 22 ]. Kang et al [ 23 ] showed that LDL-C and transcranial Doppler (TCD) detection can predict the occurrence of ischemic cerebrovascular disease, which has high application value for early diagnosis and intervention of ICVD. Liu et al [ 24 ] documented that the serum chemerin expression level was increased in patients with acute cerebral infarction, which can be used as a biological diagnostic marker for acute cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of Hcy and ICVD are as follows: (1) Hcy is able to damage vascular endothelium; (2) Hcy can stimulate the abnormal proliferation of vascular smooth muscle cells; (3) Hcy can cause platelet aggregation, change blood viscosity and increase blood coagulation; (4) Hcy is able to enhance the peroxidation of LDL-C, increase the production of LDL-C, accelerate the progression of atherosclerosis, hence aggravate the condition of ICVD [ 22 ]. Kang et al [ 23 ] showed that LDL-C and transcranial Doppler (TCD) detection can predict the occurrence of ischemic cerebrovascular disease, which has high application value for early diagnosis and intervention of ICVD. Liu et al [ 24 ] documented that the serum chemerin expression level was increased in patients with acute cerebral infarction, which can be used as a biological diagnostic marker for acute cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia was defined as a SUA level ≥420 μmol/L for men and ≥360 μmol/L for women [ 24 ], which was the cutoff in the formula. If the values of the cumulative burdens between 2 consecutive examinations were less than 0 this value would be considered as 0 [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This research determined the cutoff value for the receiver operating characteristic curve (110.6) using R software ( www.r-project.org ). The value was considered 0 when the values between two consecutive examinations were < 0, as described previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%